Can Increase in the Share of Renewable Energy in Economic Growth Shift Turning Point of EKC? Evidence from Time-series Analysis in India - Tanti, Purna Chandra; Srujana, Illa Sai; Jena, Pradyot Ranjan (Journal of Environmental Accounting and Management, 2026)
Global warming has a massive bearing on living beings, the country and environment alike. The primary perpetrator of global warming is carbon dioxide emission. This paper tries to find out the interrelationship between GDP growth and carbon dioxide emissions and the potential of renewable energy use to reduce carbon dioxide emission from industrial activities in the short and long-run. The interrelationship between GDP growth and CO2 emission has traced in this paper. Auto-Regressive Distributive Lag of cointegration model has been used to show the causal relationship among growth variables and CO2 emission. The long-run and short-run relationship of variables have been analyzed by using time series data from 1971 to 2016. This study basically focuses on the existence of EKC in India. One of the objectives of this paper is to find out the existence of renewable energy to reduce CO2 emission in India. The Positive coefficient of renewable energy seen in the findings of the study could be due to the lack of data and also due to the limited renewable resources in India during that period. It has also been noticed that energy consumption and urban population have a negative impact air pollution parameter, thus directing towards higher emission standards and emphasizing the need for transforming fossil fuel-based energy profile into one of renewable energy. The results of the study on trade openness and renewable energy suggest that India should moderate its levels of energy-intensive trade and focus on a trade involving clean energy technologies, which can be sustained only by increasing endogenous renewable energy capacity.